Proposta de modelo físico-socioambiental para o estudo de bacias hidrográficas semiáridas do nordeste setentrional (Brasil) - Lourenço, Ronaldo Mendes (2018)
The formulation and application of the “Proposal of a socio-environmental physical model for the study of the semi-arid hydrographic basin of the Northeast of Brazil" had aimed to analyze the situation of environmental degradation of the Cruxati river watershed in the state of Ceará, the pilot unity of this study. The model is represented by State of Physical-Environmental Degradation (SFED) which involves the following elements: i) Regressive Dynamics of the Plant Cover for the periods of 1985, 2001 and 2015; ii) Regressive Dynamics of Exposed Soils / Agricultural Use for the periods of 1985, 2001 and 2015; iii) Climatic Severity (CS); iv) Mean Slope (MS); v) Rainfall Erosivity (R); and vi) Erodibility of Soils (K). Aiming to demonstrate the socioeconomic and socio - environmental scenario of the studied region, the State of Socioeconomic and Socio - environmental Pressure (SSSP) was created, which demonstrates through qualitative and quantitative interactions matrices, the results obtained in the study area, the matrices are: i) Qualitative Matrix of Regressive and Progressive Dynamics of Impact (QMRPDI); ii) Matrix of Socio-Environmental Interference (MSI); iii) Socioeconomic / Agricultural and Agro-extractive Dynamics Matrix (AADM); and iv) Sustainability, Management and Environmental Planning Matrix (SMEPM). Amid the methodological procedures used, it is possible to emphasize the survey of the bibliographical and documentary material about the study area, the production of geographic and cartographic materials and the carrying out of fieldwork. The results attained by the application of SFED and SSSP indicate an advance of degradation processes in the studied region, as well as reveals the inefficiency of the management process and environment planning of the city inserted in the watershed that supported the construction of an orderly set of actions, which serve as a basis for ensuring municipal and regional environmental sustainability without the geographical context of semi-arid watersheds.